2016
DOI: 10.1080/13676261.2016.1166192
|View full text |Cite
|
Sign up to set email alerts
|

Migration aspirations of European youth in times of crisis

Abstract: In recent years, the European Union (EU) passed through a significant economic crisis. All across Europe, European young people are among the groups which are hit hardest, with youth unemployment rates rising to over 50% in member states such as Greece and Spain. In the classical migration literature, it is suggested that such unfavourable economic climate would make people more likely to move abroad. Whereas in press releases we are regularly confronted with stories about South European young adults with tert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
71
1
11

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(94 citation statements)
references
References 47 publications
11
71
1
11
Order By: Relevance
“…The group enrolled in education tends to express a higher willingness to be mobile. Van Mol () attributes this to the fact that students are freer from the constraints of everyday life and have fewer responsibilities. In their study of students' mobility intentions in Northern Ireland, Cairns and Smyth () found that more than half of those surveyed are considering living outside Northern Ireland in the future.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…The group enrolled in education tends to express a higher willingness to be mobile. Van Mol () attributes this to the fact that students are freer from the constraints of everyday life and have fewer responsibilities. In their study of students' mobility intentions in Northern Ireland, Cairns and Smyth () found that more than half of those surveyed are considering living outside Northern Ireland in the future.…”
Section: Literature Reviewmentioning
confidence: 99%
“…And yet, other more recent studies of intended future migration among students suggest that men are relatively more numerous (Cairns & Smyth, ), possibly because of family and other social constraints (Van Mol, ). There is agreement, however, that the likelihood of migration decreases with age (Epstein & Gang, ; Otrachshenko & Popova, ; Van Mol, ), marriage (Gubhaju & De Jong, ; Otrachshenko & Popova, ), and childbearing (Agadjanian, Nedoluzhko, & Kumskov, ; Hadler, ), although how these categorisations vary within the young‐adult group is less well‐documented. Previous experience of living abroad is another important factor that is associated with higher rates of mobility (Fassmann & Hintermann, : 66; Epstein & Gang, ; Tabor et al, ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The global economic crisis (GEC) (2008 and after), European refugee crisis (2014 and ongoing), the United Kingdom's decision to leave the EU (2016 and ongoing) also had profound implications for the intra‐European migratory system over the past decade (King, ). Incorporation of the Central and Eastern European (CEE) countries into the European migration system and the GEC have resulted in growing numbers of young people migrating within Europe (Cairns et al., ; Van Mol, ; King and Williams, ). Contemporary patterns reveal that migration in Europe is accelerating, including substantial return migration, and diversifying, becoming more highly variegated (King, ).…”
Section: Introductionmentioning
confidence: 99%